Science Coaching for Kompetisi Sains Madrasah (KSM) at Elementary Madrasah Level in Pati District - Affa Ardhi Saputri; Sheilla Rully Anggita; Istikomah Istikomah; Della Ayu Puspita; Siti Nurfadhilah Murtado (Konsorsium Pengetahuan Innoscientia (KOPINNOS), 2025)
The Kompetisi Sains Madrasah (KSM) is an important science competition platform for madrasah students in Indonesia, requiring comprehensive preparation for both students and supervising teachers. This community service project aimed to provide science coaching for KSM at the elementary madrasah (MI) level in Pati District, preparing teachers and students for the provincial-level competition. The training was conducted from July 16-27, 2024, through a hybrid format combining online sessions via Zoom and offline sessions at the Ministry of Religious Affairs office in Pati. Sixteen students and five supervising teachers from various madrasah ibtidaiyah in Pati District participated in the program. The training covered comprehensive science topics required for KSM, including mechanics, heat and temperature, solar system, electricity and magnetism, matter and substances, light and optics, forces, energy and energy transformation, and earth and space science. Four instructors from the Physics Department of UIN Walisongo Semarang facilitated the training, with two instructors (Istikomah and Affa Ardhi Saputri) delivering sessions fully online. In contrast, the lead instructor (Sheilla Rully Anggita) conducted both online and offline sessions. The program utilized interactive presentations, question-and-answer discussions, and intensive problem-solving practice to develop participants' conceptual understanding and competitiveness skills. Challenges encountered included limited preparation time, technical issues with equipment during online sessions, and scheduling conflicts that prevented some participants from attending complete sessions. Solutions implemented included thorough equipment testing before sessions, careful time management, and coordination to minimize scheduling conflicts. The training successfully enhanced participants' understanding of KSM requirements and equipped teachers with strategies for ongoing student coaching, demonstrating effective collaboration between higher education institutions and the Ministry of Religious Affairs to support madrasah science education.